Methodology of Teaching Dutch as a Second Foreign Language to Students - Rakhmonkulova, Khabiba Sodikovna (The Lingua Spectrum, 2026)
This article is devoted to modern approaches to teaching Dutch as a second foreign language to university students. The communicative approach, task-based learning, the dynamic (usage-based) approach, and content and language integrated learning (CLIL/LOCT) are analyzed. Examples of exercises and curriculum design are provided, along with a comparative analysis of the methods and their impact on language proficiency and learner motivation. The study demonstrates that the combination of authentic communication, work with real-life materials, and consideration of students’ individual needs leads to higher learning outcomes. The article also emphasizes that contemporary requirements for future teachers include a high level of methodological and communicative competence. Conclusions are drawn about the necessity of integrating grammatical and communicative techniques in designing NT2 courses.